Bom m 9 from Bombyx mori is a novel protein related to asthma. (July 2015) - Zuo, Jianhong; Lei, Mingsheng; Yang, Rui; Liu, Zhigang
ABSTRACT The silkworm (Bombyx mori) can cause severe IgE‐mediated allergic disease, however, the mechanism remains unclear. The aim of this study was to investigate the immunologic mechanism by which silkworms induce allergy. Whole silkworm pupa proteins were separated by SDS‐PAGE and 2‐D PAGE. Then, IgE‐binding proteins were detected by immunoblotting with sera of patients having an allergy to Bombyx mori. After tryptic digestion, the peptides of IgE‐binding proteins were analyzed by matrix‐assisted laser desorption ionization tandem time‐of‐flight mass spectrometry or tandem mass spectrometry. Database searches were used to identify allergens in silkworm pupa, after which Bom m 9 was to construct an asthma model. Thus, in the current study, a mouse asthma model was constructed with Bom m 9.